Ethical values included in biology textbooks for the secondary stage and methods of developing them from the point of view of teachers (Journal of the College of Basic Education, 2023)
The aim of the research is to find out the extent to which biology textbooks for the secondary stage include moral values and what are the appropriate methods for developing these values from the point of view of teachers.The research community consisted of all biology books for the academic year (2010-2011), as well as all biology teachers whose service period is not less than five years.The researcher used content analysis to achieve the first goal, as a criterion consisting of (25) ethical values was prepared, and to achieve the second goal, the researcher prepared a questionnaire consisting of (20) methods.Among the most prominent findings of the research is that the books of Principles of Biology for the first grade and Biology for the second grade have achieved the best results with a rate of (26.06%) and (25.32%) respectively, while the book of Biology for the fifth grade obtained the lowest percentage, which is (7.29%) In terms of methods, most of them obtained a good weighted average, as its values ranged between (2.80-2.01).In the light of the results, the researcher recommended the need to include all ethical values in the subjects of biology books for the secondary stage, in a manner commensurate with the nature of their content.